Market reaction to the Covid-19 pandemic: Events study at stocks listed on LQ45 index - Muhammad Yunus Kasim; Muslimin; I. Kadek Bellyoni Dwijaya (Cogent Business & Management, 2022)
This study aims to examine the market reaction to the Covid-19 pandemic using stocks listed on the LQ45 Index, by using the event study method to calculate and analyze the difference in Average Abnormal Return (AAR) and Trading Volume Trading (TVA) during the Covid-19 pandemic that occurred in Indonesia. The population for the study is companies listed on the LQ45 Index with a sample of 41 companies taken by purposive sampling technique. Statistical analysis was conducted by using events study with paired sample t-test in determining the abnormal return difference test for each event. The first finding was that the LQ45 stock market reacted positively since the confirmation of the Covid-19 outbreak in Wuhan, China, as investors did not consider this information bad news. Second, LQ45 shares have shown a decline since the first confirmed Covid-19 patients in Indonesia. Third, the announcement of a pandemic by the World Health Organization (WHO) continued until the Jakarta regional lockdown in April 2020 made LQ45 respond negatively. The market began to respond positively after the first vaccination in Indonesia in January 2021. Overall, the results show that the LQ45 stock market has responded quickly to the Covid-19 pandemic from the start events and responses vary over time depending on events during the pandemic. Investors tend to be quick to respond to any event so that stock movements are very difficult to project. This research concludes that the negative impact occurred on the stock market in Indonesia could be attributed to the Covid-19 pandemic.
Keywords: 650; abnormal return; covid-19 pandemic; events study; LQ45; trading volume activity